Tough Love: Do Czech Suppliers Learn from Their Relationships with Multinationals? - Beata S. Javorcik; Mariana Spatareanu (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Many countries strive to attract foreign direct investment (FDI) hoping that knowledge brought by multinationals will spill over to domestic industries and increase their productivity. While the empirical studies have cast doubt on the existence of horizontal spillovers from FDI in developing countries, several recent papers have confirmed the presence of vertical spillovers, which take place through contacts between foreign affiliates and their local suppliers. However, the existing studies rely on industry-level proxies for vertical spillovers rather than infirmation on actual relationships between local companies and multinationals. This study goes one step further by employing a unique dataset from the Czech Republic, which allows us to identify local firms supplying multinationals operating in the country. The data suggest that suppliers are different from other firms. They are larger, have a higher capital-labor ratio, pay higher wages and exhibit a higher productivity level. The evidence is suggestive of both high productivity firms having a higher probability of supplying multinationals as well as suppliers learning from their relationships with multinationals.
Keywords: F21; F23; 330; foreign direct investment; technological spillovers; suppliers; Lieferant; Lieferanten-Kunden-Beziehung; Direktinvestition; Spillover-Effekt; Produktivität; Tschechische Republik; Welt